Three new species of Acoetes (Aphroditiformia: Acoetidae) and one new species of Euarche (Aphroditiformia: Acoetidae): first Acoetes described in over three decades - Ogawa, Namy; Rizzo, Alexandra E.; Lavrado, Helena Passeri (Zootaxa, 2026)
Three new species of the genus Acoetes are described and illustrated, and a dichotomous identification key is provided. These new species from the Brazilian coast exhibit features previously unknown for the genus, such as ventral, dorsal, and elytral papillae. Acoetes pettii sp. nov., collected off Rio de Janeiro, differs from the others mainly by the morphology of a group of neurochaetae and the structure of the neuropodia. Acoetes mirandae sp. nov., collected in Espírito Santo, Brazilian southeast, is distinguished primarily by the arrangement of palpal papillae and the morphology of the parapodia. Acoetes ivisoni sp. nov., collected in Pernambuco, Brazilian northeast, differs chiefly in the morphology of the ommatophores and the projection of the aciculae. Espírito Santo and Pernambuco extend the known distribution of the family along the Brazilian coast. Based on examination of the neotype of Euarche rudipalpa (Amaral & Nonato, 1984), it was determined that the specimen actually represents a new species of the genus Euarche, based on characters such as the presence of ventral papillae and eyes morphology. In addition, the new species of Euarche reaches a depth never previously recorded for the family of 2013 m.